Ekspresi Epidermal Growth Factor Receptor dan Karakteristik Klinikohistopatologik pada Karsinoma Kolorektal - . Reallyani; Mezfi Unita; Zulkarnain Musa; Syarif Husin (Majalah Patologi Indonesia, 2015)
Background Colorectal carcinoma is one of the world's fourth most malignancies. Frequency of colorectal carcinoma malignancy most likely to occur in the gastrointestinal tract and causes the death of close to 15% of all cancers. Heterogeneous of the etiology is associated with many risk factors and molecular changes. Epidermal growth factor receptor is a 170 kDa transmembrane glycoprotein which contribute to carcinogenesis, prognostic impact and specific therapeutic targets. The aims this study to determine the relationship between EGFR expression and the clinicohistopathology characteristics in colorectal carcinoma. Methods This study is an observational study with cross sectional approach. The samples were specimens of the 57 samples that had been diagnosed as colorectal carcinoma from January 2010 to August 2012. Samples from histopathological preparations are reviewed and conducted outward EGFR immunohistochemistry with primary antibodies for the primary tumor. Results EGFR expression to histopathological characteristics are as follows pT3 of 45.6%, positive lymph node status was 52.6% and poorly differentiated histological degree of malignancy of 50.9%. Statistical calculations showed no significant correlation between EGFR expression and histopathologic characteristics of the pT in the TNM system (p=0.037), lymph node status (p=0.000), histological grading of malignancy (p=0.001), and high expression (61.4%). Conclusion EGFR expression affects the pT in TNM system, lymph node staging and histological grading of malignancy. Key words: characteristic clinicohistopathology, colorectal carcinoma, epidermal growth factor receptor.